2017
DOI: 10.21608/ijhth.2017.30229
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Accessibility of Disabled Guests' Facilities for Enhancing Accessible Tourism: Case Study of Five- Star Hotels' Websites in Alexandria

Abstract: Special issue on papers of the 10 th ICTH (2017) organized by Faculty of Tourism and Hotels, Fayoum University

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…On the supply side, 11% of the existing research has declared that lack of accessible information is indeed the primary barrier limiting disabled guests from enjoying their accomodation. Khalil and Fathy (2017) have revealed that hotel websites in Egypt offer information that is not user-friendly to disabled people.…”
Section: Challenges Of Serving Disabled Guests In Accommodation Estab...mentioning
confidence: 99%
See 2 more Smart Citations
“…On the supply side, 11% of the existing research has declared that lack of accessible information is indeed the primary barrier limiting disabled guests from enjoying their accomodation. Khalil and Fathy (2017) have revealed that hotel websites in Egypt offer information that is not user-friendly to disabled people.…”
Section: Challenges Of Serving Disabled Guests In Accommodation Estab...mentioning
confidence: 99%
“…Disabled people in African countries face a lot of challenges. These include; attitude barrier e.g., negative attitude from the community and service providers (Oladokun, Ololajulo & Oladele, 2014;Mensah, Badu & Opoku, 2015;Bombom & Abdullahi, 2016;Adam, Boakye & Kumi-Kyereme, 2017;Adam, 2019) and ignorance of service providers (Spencer & Mnqayi, 2017;Abd-Elraof, Dawood & Mohamma, 2018;Chikuta, DuPlessis & Saayman, 2018), communication barriers e.g., limited trained personnel to communicate with disabled people (Oladokun, Ololajulo & Oladele, 2014;Lwoga & Mapunda, 2017;Refaat & Ibrahim, 2017;Chikuta, Kabote&Chikaya, 2017;Chikuta, DuPlessis & Saayman, 2018), lack of clear and up-to-date information (Adam, Boakye & Kumi-Kyereme, 2017;Chikuta, DuPlessis & Saayman, 2018) and lack of user-friendly hotel websites (Khalil & Fathy, 2017); physical challenges e.g., limited facilities (Lwoga & Mapunda, 2017;Refaat & Ibrahim, 2017;Chikuta, Kabote & Chikaya, 2017), inaccessible transport systems (Bombom&Abdullahi, 2016;Chikuta, DuPlessis & Saayman, 2018), lack of appropriate tourism activities for disabled people (Chikuta, Kabote&Chikaya, 2017), and lack of accessible accommodation (Bisschoff & Breedt, 2012;Chikuta, 2015;Khumalo & Ndlovu, 2017;Mangwiro et al, 2018;Meskele, Woreta &Weldesenb, 2018). These are among the serious problems limiting disabled travelers from enjoying their trips.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation